Effective Transcranial Direct Current Stimulation Parameters for the Modulation of Eating Behavior: A Systematic Literature Review and Meta-Analysis. Issue 6 (12th July 2022) - Beaumont, Jordan D.; Smith, Natalie C.; Starr, David; Davis, Danielle; Dalton, Michelle; Nowicky, Alexander; Russell, Mark; Barwood, Martin J.
ABSTRACT: Objective: This study aimed to consider the effect of differing transcranial direct current stimulation (tDCS) parameters on eating-related measures and how issues with experimental design (e.g., inadequate blinding) or parameters variation may drive equivocal effects. Methods: Literature searches were conducted across MEDLINE, PsycINFO, Scopus, and Science Direct. Studies using conventional sham-controlled tDCS to modify eating-related measures in adult human participants were included. A total of 1135 articles were identified and screened by two independent authors. Study quality was assessed using the Risk of Bias tool. Random-effects meta-analyses were performed, with subgroup analyses to determine differences between parameter sets. Results: We identified 28 eligible studies; 7 showed low risk of bias, with the remaining studies showing bias arising from issues implementing or reporting blinding protocols. Large variation in applied parameters was found, including montage, current intensity and density, participant and researcher blinding, and the use of online or offline tasks. The application of differing parameters seemed to alter the effects of tDCS on eating-related measures, particularly for current density ( g = −0.25 to 0.31), and when comparing single-session ( g = −0.08 to 0.01) versus multisession protocols ( g = −0.34 to −0.29). Some parameters result in null effects. Conclusions: The absence of tDCS-mediated change in eating-related measures may be driven by variation in applied parameters. Consistent application of parameters that seem to be effective for modulating eating behavior is important for identifying the potential impact of tDCS. Using the findings of this review, we propose a series of parameters that researchers should apply in their work.